Generation of Kolam-Designs Based on Contextual Array P Systems - Venkat, Ibrahim; Robinson, Thamburaj; Subramanian, K. G.; de Wilde, Philippe (Diagrammatic Representation and Inference, 2018)
Kolam-designs are diagrams used to decorate the floor, especially in front of a house in South India. Methods of generation of the kolam diagrams were developed based on two-dimensional picture generating models, broadly known as array grammars, introduced for the description and analysis of picture patterns. Rewriting array P system, a membrane computing model based on array rewriting has been developed to evolve picture arrays, based on context-free array rewriting rules. In contrast to this array P system, another P system model called contextual array P system (CAP) using contextual array rules for the evolution or generation of picture arrays has been proposed and its power in generating picture arrays investigated. Here we develop an application of CAP for the generation of the kolam diagrams. The advantage of using CAP is that kolam diagrams that cannot be handled by array grammars can be generated by the CAP model.